2003
DOI: 10.1046/j.1440-1703.2003.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Microtopography and distribution of canopy trees in a subtropical evergreen broad‐leaved forest in the northern part of Okinawa Island, Japan

Abstract: The spatial distribution of trees in relation to topography was investigated using two topographic indices, slope steepness and slope configuration, in a 4‐ha plot in a subtropical evergreen forest in the northern part of Okinawa Island, Japan. Most species showed an aggregated distribution and patch size was related to various microtopographical features, including small ridges and valleys. In a cluster analysis based on the dissimilarity of each species’ distribution, the species were divided into three majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 22 publications
(24 reference statements)
9
84
0
1
Order By: Relevance
“…Wolf et al argued that aspect and slope have a considerable effect on tree species diversity, because they determine water availability [54]. Enoki found that the diversity of plant species distributed on concave and convex slopes have significant differences [55]. However, Legendre et al found that the effects of slope and aspect on distribution of richness and species composition are weak [56], similar to our results.…”
Section: Environmental Variation and Tree Diversitysupporting
confidence: 89%
“…Wolf et al argued that aspect and slope have a considerable effect on tree species diversity, because they determine water availability [54]. Enoki found that the diversity of plant species distributed on concave and convex slopes have significant differences [55]. However, Legendre et al found that the effects of slope and aspect on distribution of richness and species composition are weak [56], similar to our results.…”
Section: Environmental Variation and Tree Diversitysupporting
confidence: 89%
“…The bedrock is composed of sandstone and slate, and the forest soil is classified as a yellow soil (Y) according to the classification methods of forest soils in Japan (Morisada, 1999). This forest is dominated by Castanopsis sieboldii with a maximum height of less than 20 m. There is no history of logging or other artificial disturbance in this area during the past 50 years (Enoki, 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Os fatores edáficos, topográficos, climáticos e biológicos são os principais responsáveis pelas quedas das árvores e conseqüente abertura de clareiras (BROKAW, 1985;HALLE et al, 1978;OLDEMAN, 1974a;Oliveira-Filho et al, 1994ROBERT, 2003) e podem tornar-se mais relevantes em áreas de declividade acentuada.A topografia é considerada por alguns autores (ENOKI, 2003;LOSOS, 2004;OLIVEIRA-FILHO et al, 1994) como um dos fatores abióticos que mais influencia na estrutura de florestas tropicais em escala local, por estar fortemente correlacionada a outras variáveis ambientais, como a presença de água no solo e as características físico-químicas dos solos.…”
Section: Fatores Abióticosunclassified